LncRNA-Six1 Encodes a Micropeptide to Activate Six1 in Cis and Is Involved in Cell Proliferation and Muscle Growth - Cai, Bolin; Li, Zhenhui; Ma, Manting; Wang, Zhijun; Han, Peigong; Abdalla, Bahareldin A.; Nie, Qinghua; Zhang, Xiquan (Frontiers in Physiology, 2017)
Long noncoding RNAs (lncRNAs) play important roles in epigenetic regulation of skeletal muscle development. In our previous RNA-seq study (accession number GSE58755), we found that lncRNA-Six1 is an lncRNA that is differentially expressed between White Recessive Rock (WRR) and Xinghua (XH) chicken. In this study, we have further demonstrated that lncRNA-Six1 is located 432 bp upstream of the gene encoding the protein Six homeobox 1 (Six1). A dual-luciferase reporter assay identified that lncRNA-Six1 overlaps the Six1 proximal promoter. In lncRNA-Six1, a micropeptide of about 7.26 kDa was found to play an important role in the lncRNA-Six1 in cis activity. Overexpression of lncRNA-Six1 promoted the mRNA and protein expression level of the Six1 gene, while knockdown of lncRNA-Six1 inhibited Six1 expression. Moreover, tissue expression profiles showed that both the lncRNA-Six1 and the Six1 mRNA were highly expressed in chicken breast tissue. LncRNA-Six1 overexpression promoted cell proliferation and induced cell division. Conversely, its loss of function inhibited cell proliferation and reduced cell viability. Similar effects were observed after overexpression or knockdown of the Six1 gene. In addition, overexpression or knockdown of Six1 promoted or inhibited, respectively, the expression levels of muscle-growth-related genes, such as MYOG, MYHC, MYOD, IGF1R, and INSR. Taken together, these data demonstrate that lncRNA-Six1 carries out cis-acting regulation of the protein-encoding Six1 gene, and encodes a micropeptide to activate Six1 gene, thus promoting cell proliferation and being involved in muscle growth.